The impact of organisational structure on organisational learning - Turi, Jamshid Ali; Sorooshian, Shahryar (Inderscience Enterprises Ltd., 2019)
Focus of the research was to find out the impact of organisational structure on organisational learning and to find out which type of organisation provides better learning opportunities. Data was collected from 130 universities operating in public and private sector of Pakistan. The approach used for research was formative conceptualisation for organisational learning. The framework makes clear that organisational learning varies according to the kind of structure. The study of the different design variables allows us to expand our understanding of different organisational learning implications. Study shows that organic structural profile helps organisational learning and greater knowledge creation rather than mechanic profile. The critical variables that facilitate learning are centralisation and indoctrination. The study further responds to the need to provide empirical evidence about the influence of organisational structure on organisational learning, advancing the measure of this emergent field of management research using formative conceptualisation.